(untitled) (African Journal of Biomedical Research, 2022)
The six-minute walk test (6MWT) is a common utility outcome for evaluating exercise capacity in patients with pulmonary diseases. However, there is no existent reference value for Nigerian older adults. This study is therefore aimed at establishing reference values and equations for 45-70 years old Nigerian adults. We consecutively recruited apparently healthy adults into this cross-sectional survey and used standard protocols for 6MWT and anthropometrics. Regression equations were developed based on demographic and anthropomorphic data. These equations were compared to existing prediction equations. One hundred and four participants completed two 6MWT. The average six-minute walk distance (6MWD) was 378 metres; greater in men than women (p<0.001). The 25th and 75th percentiles were 345.10 and 408.18 metres, respectively. The variables that were significantly associated with 6MWD were sex, age and height. We found two explanatory model equations and the model equation for all participants is 6MWD = 297.96 + 47.41 (sex) – 1.001 (age) + 65.214 (height) where female = 0 and male = 1 with explanatory power of 41.3%. Applying other studies’ equations to our population resulted in an underestimation or overestimation of the 6MWD. In conclusion, the average 6MWD in this Nigerian population was 378 metres. Age, height and sex were the most significant predictors of 6MWD and the regression equations explained 41% of the variance in the distance walked. These equations will help to improve evaluation of patients with diseases that affect aerobic capacity.